Diseño e implementación de un sistema de producción agroecológica en la microcuenca las Violetas, en la Hoya de Loja - Coronel Alulima, Tatiana Nathalí (2016)
This research work was conducted in three phases: the first, consists in carrying out an assessment of the socio-ecological conditions of Las Violetas Watershed through applying a survey, the geographical and political location is established here, factors are identified such as climatic factors, water, edaphic factors, plant resources, socio-educational and economic aspects, basic services, land tenure, inputs, livestock, It also elaborated a SWOT (Strengths, Weaknesses, Opportunities and Threats) and finally a model farm is identified. In the second phase, an agro-ecological system model is designed for a farm in the study area using a geographic information software, for which It starts from the diagnosis of the model farm chosen and It’s elaborated the agro-ecological design proposal based in the manual of the Red Agro-ecological de Loja (RAL), , which consists of five components like soil component, crops component, water component, tree component, animal component and family component. For the third phase, It is implemented a component of agro-ecological design in the chosen farm based on the farm owner’s interest, it sets the silvopastoral system proposed in the design which has the following aspects like scattered trees, alder trees were used:, of the estate of, is implemented (Alnus acuminata Kunth) and guato stakes (Erythrina edulis Micheli); a fodder bank, which was established with maralfalfa (Pennisetum violaceum (Lam) Rich..); and improved pastures with enrichment of the current pasture by planting red clover (Trifolium pratense L.). Finally, it socializes the results of all research with residents of the Las Violetas Watershed and students of the Agricultural Engineering Career.